1998
DOI: 10.1159/000022792
|View full text |Cite
|
Sign up to set email alerts
|

Effect of α-Gene Numbers on the Expression of β-Thalassemia intermedia, β-Thalassemia and (δβ)°-Thalassemia Traits

Abstract: The effects of variations in α-gene numbers on phenotypical expression of β-thalassemia are assessed in 11 subjects of 8 families. The study indicates that coexistence of α-thalassemia (–α3.7/αα) decreases the HbF in IVSI-6 homozygote and in δβ-thalassemia trait and may ameliorate the disease in β-thalassemia compound heterozygotes associated with one mild and one severe β-thalassemia mutation. Coexistence of α-gene triplication is associated with an increase in HbF value and may increase the severi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
4
0
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 26 publications
2
4
0
1
Order By: Relevance
“…Mean value of hemoglobin (P < 0.001), reticulocytes (P < 0.001), and red cell indices were statistically significant in the compared groups. Coexistence of the α-thalassemia (−α 3.7/ α α) modified the expression of homozygosity for IVSI-6 mutation in such a way that there were higher hemoglobin and lower HbF levels as compared to those without αthalassemia (29). A similar effect of the homozygosity of α-thalassemia on HbF value was previously observed in patients with sickle cell anemia (30).…”
Section: Discussionsupporting
confidence: 63%
“…Mean value of hemoglobin (P < 0.001), reticulocytes (P < 0.001), and red cell indices were statistically significant in the compared groups. Coexistence of the α-thalassemia (−α 3.7/ α α) modified the expression of homozygosity for IVSI-6 mutation in such a way that there were higher hemoglobin and lower HbF levels as compared to those without αthalassemia (29). A similar effect of the homozygosity of α-thalassemia on HbF value was previously observed in patients with sickle cell anemia (30).…”
Section: Discussionsupporting
confidence: 63%
“…However, the number of studies investigating clinical features of α-thalassemia is limited; with the primary focus of these studies generally being to investigate the effects of α-globin gene mutations on clinical severity of β-thalassemia or sickle cell disease [7,8,[11][12][13]32]. In a study by Guvenc et al [8], a higher rate of coexisting α-thalassemia mutations with β-globin chain abnormalities were detected.…”
Section: Resultsmentioning
confidence: 99%
“…This could be because the children are also α-thalassemia carriers (-α 3.7 /αα). A study carried out on the effect of α-gene numbers on the expression of β-thalassemia indicated that the coexistence of α-thalassemia (-α 3.7 /αα) may ameliorate the disease in β-thalassemia compound heterozygotes [21]. …”
Section: Discussionmentioning
confidence: 99%